Repetitive transcranial magnetic stimulation and transcranial direct-current stimulation in neuropathic pain due to radiculopathy: a randomized sham-controlled comparative study. Issue 6 (June 2016) - Attal, Nadine; Ayache, Samar S.; Ciampi De Andrade, Daniel; Mhalla, Alaa; Baudic, Sophie; Jazat, Frédérique; Ahdab, Rechdi; Neves, Danusa O.; Sorel, Marc; Lefaucheur, Jean-Pascal; Bouhassira, Didier
Abstract : Abstract: No study has directly compared the effectiveness of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct-current stimulation (tDCS) in neuropathic pain (NP). In this 2-centre randomised double-blind sham-controlled study, we compared the efficacy of 10-Hz rTMS and anodal 2-mA tDCS of the motor cortex and sham stimulation contralateral to the painful area (3 daily sessions) in patients with NP due to lumbosacral radiculopathy. Average pain intensity (primary outcome) was evaluated after each session and 5 days later. Secondary outcomes included neuropathic symptoms and thermal pain thresholds for the upper limbs. We used an innovative design that minimised bias by randomly assigning patients to 1 of 2 groups: active rTMS and tDCS or sham rTMS and tDCS. For each treatment group (active or sham), the order of the sessions was again randomised according to a crossover design. In total, 51 patients were screened and 35 (51% women) were randomized. Active rTMS was superior to tDCS and sham in pain intensity (F = 2.89 and P = 0.023). Transcranial direct-current stimulation was not superior to sham, but its analgesic effects were correlated to that of rTMS ( P = 0.046), suggesting common mechanisms of action. Repetitive transcranial magnetic stimulation lowered cold pain thresholds ( P = 0.04) and its effect on cold pain was correlated with its analgesic efficacy ( P = 0.006). However, rTMS had no impact on individual neuropathic symptoms. Thus, rTMS is more effective than tDCS and sham in patients with NP due to lumbosacral radiculopathy and may modulate the sensory and affective dimensions of pain. Abstract : In this randomized placebo-controlled study, 10-Hz rTMS of the motor cortex induced a higher analgesic effect than sham and 2-mA tDCS in painful radiculopathy.